The Role of Sufism as Social Piety and Individual Piety for the Young Generation: Study Pondok Pesantren Tasawuf Underground - mursalat mursalat (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2023)
Many people think that Punk is a deviant behavior, a nuisance, synonymous with violence, a free lifestyle, closely related to drugs, free sex, thuggery, and so on which gives a negative stigma. Punk children who are members of the underground Sufism community, have learned and made themselves better, this indicates that not all punk children are negative like what is stigmatized by society. This study aims to find out how the background of the underground Sufism community, as well as how the underground Sufism community can be close and change punk children by applying appropriate educational methods. And to find out what the punk kids are learning as well as what good changes are happening in their lives. The research method used in this research is descriptive qualitative research method by interpreting phenomena that occur and are carried out, involving existing methods. In qualitative research, the methods commonly used are interviews, observations, and the use of documents. The results of this study concluded that the da'wah strategy carried out by Ustadz Halim Ambiya in fostering punk children in the Tasawuf Underground community, for the first time, took an individual persuasive approach to punk children, by being present as a friend, offering the concept of love and affection, taking the role of a father. and introduce the road map back to God and family. The da'wah guidance carried out by Ustadz Halim focused on releasing alcohol, drugs, sex, and other crimes, by conducting psychotherapy following tariqoh qadariyah wa naqsybandiyah (TQN) Suryalaya with the concept of al-inabah. In his coaching of punk children, Ustadz Halim uses both formal and non-formal teaching methods and uses social and economic empowerment methods